2017
DOI: 10.1021/acs.chemmater.7b00764
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Iron(II) Pyrosilicate Na2Fe2Si2O7: A Potential Cathode Material in the Na2O-FeO-SiO2 System

Abstract: As lithium-ion battery technology becomes widely popular with increasing demand for efficient energy-storage devices for a wide range of applications, the scarcity of lithium resources poses a concern for increasing costs. Replacing lithium with much more abundant sodium in combination with abundant transition metals such as iron (instead of traditionally used cobalt or nickel) as the charge compensation center in the cathode materials is expected to make large-scale battery technology a reality. To activate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Electrochemical testing indicated, however, that the electrochemical activity could be improved in subsequent studies. [206] Considering the high Coulombic efficiency and high reversible capacity, this iron sulfate composite deserves more exploration to achieve a good understanding of the local structure as well as the design of the morphology. Na 2 MnSiO 4 is another great choice for a low-cost silicatebased electrode for SIBs.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…Electrochemical testing indicated, however, that the electrochemical activity could be improved in subsequent studies. [206] Considering the high Coulombic efficiency and high reversible capacity, this iron sulfate composite deserves more exploration to achieve a good understanding of the local structure as well as the design of the morphology. Na 2 MnSiO 4 is another great choice for a low-cost silicatebased electrode for SIBs.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…In early 2017, Panigrahi et al reported on a new Na 2 Fe 2 Si 2 O 7 orthosilicate, which was synthesized via a classic solid-sate reaction. [185] Density functional theory (DFT) calculations predicted redox voltages between 2.23 and 2.56 V versus Na/Na + , which lie in the electrolyte stability window and thus make this compound a potential cathode material for Na-ion batteries. Na 2 Fe 2 Si 2 O 7 crystallizes in the monoclinic P12 1 /n1 unit cell and consists of 1D chains, which are built out of corner-and edge-sharing distorted FeO 5 bipyramids and FeO 4 tetrahedra (Figure 16a).…”
Section: Orthosilicate Na 2 Fe 2 Si 2 Omentioning
confidence: 99%
“…2018, 8, 1703055 Reproduced with permission. [185] Copyright 2017, American Chemical Society. Figure 17.…”
Section: Compositional Strategymentioning
confidence: 99%
“…Nevertheless, most of the polyanionic compounds suffer from inherent low electronic conductivity, and therefore a well-decorated carbon coating and network are essential for their C-rate performance. According to the previous report, the majority of polyanionic composites possess one-or two-dimensional (1D or 2D) sodium diffusion pathways (Kim et al, 2013(Kim et al, , 2015Chen M. et al, 2017;Panigrahi et al, 2017;Chen et al, 2018;Fang et al, 2018;Zhu et al, 2019). The low-dimensional sodium diffusion pathways cannot guarantee satisfactory C-rate capabilities, especially in low temperature environments.…”
Section: Polyanionic Compounds With 3d Na + Diffusion Pathwaysmentioning
confidence: 99%